Attitudes toward research and its impact to research skills development among Grade 12 students of Meycauayan National High School - Serrano, Erickson (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
The primary concern of this research paper was to relate how Grade 12 students of Meycauayan National High School perceived research subjects such as Practical Research 2 and how these attitudes toward research affected their research skills development. With the purpose of bridging the link between the affective domains of learning to how students develop their research skills, the researcher used the Attitude Towards Research (ATR) Scale developed by Papanastasiou (2002) and a Research Skills Assessment Test based on Gilmore and Feldon (2010). These instruments were administered to 60 Grade 12 Senior High School students of MNHS across different strands, while accompanied with Active Learning Classroom Strategies in teaching Practical Research 2. Through pre-test and post-test design, the researcher evaluated the impact of the students’ attitudes toward research in five (5) factors. These five factors were generalized as Post-ATR and was correlated to the Final Grades of the respondents in Practical Research 2. Upon data analysis using t-test and correlational statistics, it was highlighted that participants were more focused on how Research subjects are with utmost relevance and usefulness to their everyday lives, though, many of them still gave concern on anxiety and difficulty of the subject. It was also evident that in general, how students feel about research has a great impact on how they develop their research skills along the course. Through this study that found that improved attitudes toward research significantly increased the students’ research skill and with the help of the data analyzed in this paper, the researcher encourage teachers to not only focus on students’ cognitive and psychomotor skills but to give equal importance as well with the attitudes toward research as these would contribute to students’ overall research skill development.